2014
DOI: 10.1177/1089253214553066
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Anesthesia and Critical Care Medicine

Abstract: The rotation of the earth and associated alternating cycles of light and dark–the basis of our circadian rhythms–are fundamental to human biology and culture. However, it was not until 1971 that researchers first began to describe the molecular mechanisms for the circadian system. During the last few years, groundbreaking research has revealed a multitude of circadian genes affecting a variety of clinical diseases, including diabetes, obesity, sepsis, cardiac ischemia, and sudden cardiac death. Anesthesiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 141 publications
(217 reference statements)
1
42
0
1
Order By: Relevance
“…Circadian rhythms are regulated by peripheral and central clock genes (27). Disruption of clock genes and circadian de-synchrony have been associated with metabolic pathologies, increased risk for morbidities, (obesity, diabetes) (27), and may influence sepsis (28). The absence or disruption of circadian rhythms in critically ill patients is possibly unfavorable and a potential therapeutic target (28).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian rhythms are regulated by peripheral and central clock genes (27). Disruption of clock genes and circadian de-synchrony have been associated with metabolic pathologies, increased risk for morbidities, (obesity, diabetes) (27), and may influence sepsis (28). The absence or disruption of circadian rhythms in critically ill patients is possibly unfavorable and a potential therapeutic target (28).…”
Section: Discussionmentioning
confidence: 99%
“…during sepsis, heart ischemia or lung disease), the need to monitor light or to treat disrupted circadian rhythms has not been introduced into clinical practice yet. During the last few years, groundbreaking research has revealed a multitude of circadian genes affecting a variety of clinical diseases, including diabetes, obesity, sepsis, cardiac ischemia, and sudden cardiac death (2, 4, 5). Interestingly, the ICU environment in particular has been shown to disrupt the circadian system of patients (2).…”
mentioning
confidence: 99%
“…During the last few years, groundbreaking research has revealed a multitude of circadian genes affecting a variety of clinical diseases, including diabetes, obesity, sepsis, cardiac ischemia, and sudden cardiac death (2, 4, 5). Interestingly, the ICU environment in particular has been shown to disrupt the circadian system of patients (2). Newly acquired knowledge of circadian rhythms could now lead to changes in clinical practice and new therapeutic concepts for critical illness and associated diseases and complications.…”
mentioning
confidence: 99%
See 2 more Smart Citations